Critical Agent, Deliberative Democracy, and Reason-Giving (2020)
This paper aims at proposing a concept of a critical agent in dialogue with the practice of deliberative democracy, considering what reason-giving means. For this purpose, this paper first discusses what being or tending to be critical of oneself or third parties would mean. This section mainly draws on ideas from the theory of argumentation and informal logic. Second, the concept of deliberative democracy is addressed in light of the conceptual synergy that would be the result of the (potential) participation of a critical agent in such a sociopolitical context. This section examines some of the core ideas within the theory of deliberative democracy. Subsequently, the third and last section discusses Brandom’s inferentialist semantic proposal (2002, 2005) to address the problem of giving and receiving reason and see how this approach can contribute to a deliberation theory and a concept (and the education) of a critical agent. The conclusion section summarizes the main ideas and offers a counterpoint between the notion of agency, an important notion in my proposal, and the idea of person, a particularly valuable aspect in the theory of deliberative democracy.